Penentuan Bidang Gelincir Longsoran berdasarkan Karakteristik Fisis Batuan dengan Seismik Bias Dangkal di Daerah Cililin, Bandung - Marjiyono, Marjiyono; Soehaimi, Asdani; H. Setiawan, Januar (Pusat Survei Geologi, 2006)
Hazard history of the Cililin area shows that landslides often occur there. Seismic refraction measurement has been aimed at detecting the existence of sliding planes in this area. Hagiwara method was applied for calculating the depth of layers beneath each geophone. The result of the analysis shows that the thickness of the layer which is potential to sliding is about 1.4 m in average consisting of thallus and weathering material of tuffaceous sandstone . Keyword : landslide, seismic refraction, sliding plane